2020
DOI: 10.1055/s-0039-1690846
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Reactivity, and Synthetic Applications of Sodium Diisopropylamide

Abstract: The 60-year history of sodium diisopropylamide (NaDA) is described herein. We review various preparations, solvent-dependent stabilities, and solution structures. Synthetic applications of NaDA reported to date are framed by a mechanism-driven approach, emphasizing selectivities when appropriate. We conclude with examples beyond metalation in which NaDA plays a central role and with a few thoughts on where future applications could be focused.1 Introduction2 Preparation and Physical Properties3 Solution Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…A common strategy to increase the solubility and enhance the reactivity of polar organometallic reagents and s‐block metal amides is the use of Lewis donor additives [19] . In this regard, Collum has assessed the constitution of sodium amides NaHMDS (HMDS=1,1,1,3,3,3‐hexamethyldisilazide) and NaDA (DA=diisopropylamide) in several solvents in the presence of a variety of donor additives and investigated their reactivity in organic transformations such as dehydrohalogenation and metalation [12, 20, 21] . Recently we have shown that NaTMP (TMP=2,2′,6,6′‐tetramethylpiperidide) combined with the tridentate donor PMDETA ( N,N,N′,N′′,N′′‐ pentamethyldiethylenetriamine) and B(O i Pr) 3 can promote the regioselective borylation of non‐activated substrates, offering in some cases complementary selectivities to those observed using transition‐metal catalysed protocols [22] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common strategy to increase the solubility and enhance the reactivity of polar organometallic reagents and s‐block metal amides is the use of Lewis donor additives [19] . In this regard, Collum has assessed the constitution of sodium amides NaHMDS (HMDS=1,1,1,3,3,3‐hexamethyldisilazide) and NaDA (DA=diisopropylamide) in several solvents in the presence of a variety of donor additives and investigated their reactivity in organic transformations such as dehydrohalogenation and metalation [12, 20, 21] . Recently we have shown that NaTMP (TMP=2,2′,6,6′‐tetramethylpiperidide) combined with the tridentate donor PMDETA ( N,N,N′,N′′,N′′‐ pentamethyldiethylenetriamine) and B(O i Pr) 3 can promote the regioselective borylation of non‐activated substrates, offering in some cases complementary selectivities to those observed using transition‐metal catalysed protocols [22] .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Recent advances in the field have started to address some of these limitations, supporting the vision of a future more sustainable polar organometallic chemistry for functionalising aromatic molecules (Figure 1b). [11][12][13][14] Figure 1. Examples of reactivity of alkyl-sodium reagents in sodiumhalogen exchange and deprotonative sodiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the field have started to address some of these limitations, supporting the vision of a future more sustainable polar organometallic chemistry for functionalising aromatic molecules (Figure 1b). [11–14] …”
Section: Introductionmentioning
confidence: 99%
“…The Oppolzer enolates merged our interest in understanding the structure–reactivity-selectivity relationships of alkali metal enolates 2 with efforts to promote the long-overlooked potential of organosodium chemistry. 3 …”
Section: Introductionmentioning
confidence: 99%